Rancang Bangun Sistem Informasi Penggajian Guru dan Pegawai di MA Al-Hidayah Cikancung - Ujang Robi; Encep Supriatna; Tonton Taufik Rachman (Jurnal Dimamu, 2021)
The design of the teacher and employee payroll information system is a system created to facilitate treasurers in managing teacher and employee salary data, for example for attendance which is currently still managed manually and salary calculations are still semi-computerized which are at risk of miscalculation of both the number of days for teachers and employees. incoming employees or the salary itself, reporting takes a lot of time and duplication of data can also occur. This information system uses the SDLC (System Development Life Cycle) for system design methodology, and the writing methodology used is descriptive method, to obtain data using the methods of observation, interviews, and literature study. To design this payroll information system is to use several design tools, including Data Flow Diagrams, Structure Charts, Flowmaps, and ER Diagrams. The development of this information system uses the Microsoft Visual Foxpro 9.0 programming language and is divided into three modules, namely master, transaction, and report. The design of this payroll information system is expected to improve the performance of the treasurer in the management of teacher and employee salaries involving attendance and deductions, and make it easier to make attendance reports, assignments, deductions, and payroll.